2012年夏季挪威海和格陵兰海浮游植物群落结构的色素表征 - 王肖颖; 张芳; 李娟英; 林凌; 高源; 何剑锋 (2014)
对2012年中国第5次北极科学考察期间的挪威海和格陵兰海两个断面的光合色素进行了高效液相色谱(HPlC)分级分析,通过藻类色素化学分类分析软件(CHEMTAX)获得了不同浮游植物类群对叶绿素A的贡献,进而得到该海域表层和次表层(30 M)的浮游植物群落结构。结果表明:表层总叶绿素A的浓度为23.59 ng/l,低于次表层的30.38 ng/l,其中浮游植物根据粒径划分对总叶绿素A的贡献由高到低依次是微型浮游植物、小型浮游植物和微微型浮游植物。该海域同时存在葱绿叶绿素(PrASInO)、墨角藻黄素(fuCO)、别藻黄素(AllO)、多甲藻素(PErId)、玉米黄素(zEA)、19-丁墨甲藻黄素(19'bf)和19-六已墨甲藻黄素(19'Hf)等色素,其浓度和分布与温盐和营养盐等环境因子存在一定的相关性。不同粒径浮游植物色素组成显示,微微型浮游植物群落中以S型定鞭藻(28%)、n型定鞭藻(21%)、硅藻(18%)和青绿藻(12%)占优;微型浮游植物群落的优势类群为S型定鞭藻(53%)、n型定鞭藻(20%)和硅藻(12%);而小型浮游植物群落主要为硅藻(63%)和甲藻(17%)。 Composition of phytoplankton controlled not only the formation of the Food Chain,but also the efficiency of energy transfer.At the same time,phytoplankton influenced the distribution of nutrient and the sedimentation of organic particulate matter.So study of phytoplankton community structures plays an important role in understanding the ecological function of phytoplankton.Photosynthetic pigments needed by photosynthesis,are very good biomarkers.They can be used to research and characterize phytoplankton community structure.Norwegian and Greenland Seas which are influenced by the Arctic water with low temperature and salinity and Atlantic water with high temperature and salinity.Understanding of correlation between environmental factors and phytoplankton community structure,is important for understanding the community structure of the marine organisms and their ecological function.During the 5thChinese Arctic Research Expedition in summer 2012,we analyze the photosynthetic pigments fromNorwegian and Greenland Seas by HPLC.Contributions of different phytoplankton assemblages to Chlorophyll a were obtained by Chemical Taxonomy( CHEMTAX),and thus resulted in composition of the phytoplankton community structure at the surface and subsurface water( about 30 m depth).The result showed that average concentration of Chlorophyll a at surface water was 23.59 ng / L,lower than that at upper water( 30.38 ng / L).The contributions of phytoplankton to Chlorophyll a were nano-> micro-> pico-one.Prasinoxanthin,Fucoxanthin,Alloxanthoxyletin,Peridinin,Zeaxanthin,19'-but-fucoxanthin,19-hexanoyloxyfucoxanthin were observed in the waters.Their distributions were relative to environmental factors,including Nutrients,temperature and salinity.These photosynthetic pigments showed negative correlations with temperature and salinity.Whereas they showed positive relations with nutrients,including NO-2,NO-3,SiO3 2-and PO3-4.The correlations of different phytoplankton and environmental factors were different.Diatoms had a very significant positive correlation with SiO3 2-,but had no correlation with PO3-4,NO-2and NO-3; Haptophytes-N had significant positive correlations with PO3-4,NO-2and NO-3; Haptophytes-S also had a positive correlation with PO3-4,but had no correlation with NO-2and NO-3.The maximum values of these photosynthetic pigments,except for Zea and Fuco,existed in the subsurface of the section BB.The distribution and concentration of photosynthetic pigments could explain the distribution and abundance of the phytoplankton to some extent.Not only because the pigments are complex and multiple,but also because there are inevitable errors in the testing and sampling,we cant determine the existence and abundance of the phytoplankton.So we use the CHEMTAX to obtain the contributions of different phytoplankton assemblages to Chlorophyll a,and thus resulted in composition of phytoplankton community structure.The composition of phytoplankton showed that Haptophytes-S( 28%), Haptophytes-N( 21%),Diatoms( 18%),and Prasinophytes( 12%) were main assemblages in the picoplankton; the main composition of nanophytoplankton were Haptophytes-S( 53%),Haptophytes-N( 20%),and Diatoms( 12%); meanwhile, Diatoms( 63%) dominated the microphytoplankton,followed by Dinoflagellates( 17%).Haptophytes-S,Haptophytes-N and Diatoms were dominant species in the surface and subsurface of section BB and AT belonging to the Norwegian and Greenland Sea.If Fucoxanthins and Diatomss existence in picophytoplankton could explain the tendency of phytoplankton to micro and miniaturization,these still need to be more sufficient evidence. 国家自然科学基金(41076130;41206189); 南北极环境综合考察与评价专项(CHINARE2011-2015)